The political trial and freedom of expression (Revista do Tribunal Regional Federal da 3ª Região, 2011)
The recent decision of the Brazilian Supreme Court, referring to what became known as “march of marijuana,” represents a  ilestone in the history of the country, regarding the right to freedom of expression. Brazil is still far, however, from the concept given to the institute by the United States Supreme Court. Moreover, it is questionable whether the Brazilian Supreme Court decided in order to honor freedom of speech, or if freedom of expression has served as a resource to legitimize a political decision.
Keywords: freedom of expression×political trial×marijuana march×individual guarantees×